IMPLEMENTACIÓN Y ESTANDARIZACIÓN DE LA TÉCNICA PARA LA DETERMINACIÓN DE POTENCIA MICROBIOLÓGICA DE NEOMICINA EN CREMA TÓPICA FABRICADA EN UNA PLANTA PRODUCTORA DE MEDICAMENTOS (2003)
The analytical procedure for determination of microbiological potency of neomycin in topical crearn was standardized and implemented. In order to that originating sarnples of three pilot batches of the product wereanalyzed, the sarnples were stored in the following conditions: 20•c-60% relative humidity, 30"C-70% relative hurnidity and 40•C-80% relative hurnidity. Nine processings settled down as it bases of the experimental design, which consisted of resulting combinations of the method of extraction of the sarnple with the conditions of storage. In order to separate the analito of interest of the product extraction with ether was used, extraction with ch!oroform and separation with ultrasound equipment. The method used in the analysis was the biological assay described by the USP. The obtain results showed that the processuigs with ether were adequated for the extractionof the sarnple since they presented inhibition zones similar to those of the standard with which they were éompared, the used methods were cylinder-plate ''plate" and discs in culture media.